2015
DOI: 10.1097/cad.0000000000000226
|View full text |Cite
|
Sign up to set email alerts
|

N-[4-(4,6-Dimethyl-2-pyrimidinyloxy)-3-methylphenyl]-N′-[2-(dimethylamino)] benzoylurea induces cell-cycle arrest and apoptosis in human cancer cells

Abstract: N-[4-(4,6-Dimethyl-2-pyrimidinyloxy)-3-methylphenyl]-N'-[2-(dimethylamino)]benzoylurea (SUD) is a novel synthesized benzoylurea derivative. We selected several human cancer cell lines to investigate whether SUD can inhibit the growth of cancer cells. We selected the liver cell line L-02 to investigate the effect of SUD on the normal cells. Flow cytometric analysis was used to detect the effect of SUD on cell cycle, Hoechst 33258 staining was used to evaluate the apoptosis induced by SUD, real-time fluorescence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…The activation of CDK1 is critical to the cell cycle of the transition from the G2 to M phase. [ 3 , 6 ] Chk1 inhibits the Cdc25a activity meanwhile Cdc25a promotes activation of CDK1 [ 7 , 8 ]. Our result demonstrated that DDTC reduced the expression level of Cdc25a and CDK1 and increased Chk1 expression.…”
Section: Discussionmentioning
confidence: 99%
“…The activation of CDK1 is critical to the cell cycle of the transition from the G2 to M phase. [ 3 , 6 ] Chk1 inhibits the Cdc25a activity meanwhile Cdc25a promotes activation of CDK1 [ 7 , 8 ]. Our result demonstrated that DDTC reduced the expression level of Cdc25a and CDK1 and increased Chk1 expression.…”
Section: Discussionmentioning
confidence: 99%